Effects of lower limb muscle isometric strength on the 3000m skating speed and energy metabolism characteristics of Chinese elite female speed skaters - Zou, X.; Zhang, K.; Wang, Y.; Shi, D.; Zhang, D. (Research Square, 2023)
The objective was to investigate the effect of lower limb muscle isometric strength on speed skating specialized characteristics in elite female speed skaters. Three China speed skaters were subjects (mean age 18.0 ± 1.4) with a mean best score (4'18.9). The isometric mid-thigh pull (IMTP) method was used to test peak force (PF), relative peak force (RPF), rate of force development (RFD), and impulse (IMP) of the lower limb muscles from 0-250ms in June 2021 at the national training base in Qinhuangdao, China. It was concluded that the force-time curves of the athletes' isometric mid-thigh pull (IMTP) exhibited varying elevated and decaying time distribution characteristics. Combined with the skating characteristics of athletes in 3000m Competition, it was found that peak force (PF) and relative peak force (RPF) are important factors affecting average skating speed, rate of change of speed, starting speed, maximum speed and speed endurance. Therefore, the IMTP test can be used as an effective method for preliminary assessment of specific strength and skating ability in the early training of speed skaters while providing effective data support for individualized lower limb strength training and specific technical training..